IbM Guru SD dalam Pembuatan Media 3D untuk Pengajaran Bahasa Inggris - Siti Syafi'atul Qomariah; Dira Permana; Baiq Zuhrotun Nafisah (Universitas Pendidikan Mandalika (UNDIKMA), 2016)
This IbM program aimed to help teachers of both schools in making application of 3D especially inEnglish learning. This program was conducted at SDN 1 Langko and SDN 2 Langko Janapria Central Lombok.SDN 1 Langko had 12 teachers, 94 students and 1 staff, then SDN 2 Langko had 12 teachers, 240 students and1 staff. The steps which was conducted were requirement (determined tools), designing, coding, testing andimplementing. The result of this public services was application which could be used by English teachers inimproving quality of students’ learning.